Ethics in pastoral ministry - Gula, Richard M. (Mahwah, NJ Paulist, 1995)
Includes biliographical references and index.
Keywords: Clergy -- professional ethics; Sexual misconduct by clergy; Confidential communications -- clergy; Pastoral theology -- Catholic church